Potensi Obat Kumur Ekstrak Daun Seledri dalam Menghambat Pertumbuhan Bakteri Streptococcus Mutans: (Uji Laboratorium) - Astri Annur Qalbi; Nurul Annisa; Febi Magfirah; St. Nur Eni; Aisyah AR; Siti Alfah (Lembaga Pengembangan Kinerja Dosen, 2024)
Caries is caused by microbial activity of a fermented carbohydrate. The results of Basic Health Research (RISKESDAS) state that the largest proportion of dental problems in Indonesia are damaged/cavities/sick teeth (45.3%). Preventive efforts gargling mouthwash contains antibacterial, long-term use has side effects, so we need herbal ingredients that have antibacterial properties, one of which is celery leaves. This study aims to prove the potential of celery leaf extract (Apium graveolens L.) as a mouthwash ingredient in inhibiting the growth of caries-causing bacteria and being able to reduce the number of bacterial colonies compared to formulary controls without active ingredients. This type of research used laboratory and field experiments with pretest-posttest consisting of the intervention group of celery leaf extract mouthwash formulation concentrations of 30%, 15% and control formulary without active ingredients, the sample consisted of 39 people, the sample was rinsed for 1 minute. Saliva collection before and after gargling. The variables studied the inhibition of bacteria. The results of the inhibition of Streptococcus mutans bacteria carried out by the ANOVA test at a concentration of 15% showed a mean of 5 mm and a concentration of 30% with a mean of 6.2 mm with a p-value of 0.000 which means that there was a significant difference in inhibiting Streptococcus mutans bacteria, while the control had a mean of 0. 0 mm which means there is no resistance formed. The conclusion of this study is that giving celery leaf extract mouthwash Calculate the inhibition zone with a concentration of 15%, 30% being able to inhibit bacteria while the control has no inhibition on Streptococcus mutans bacteria.